Mentre il corpo cammina. Eidos dello sport e attività fisica elementare - Emanuela Ferreri (SHARE Press, 2023)
The essay offers a reflection on the eidos of sport (body-game-movement) and the elementary movement of walking. It is crossing some examples of the study of movement and attention practices. Pedestrian hiking in the environment (with reference to the ecology of social relations by T. Ingold); the mindfull walking, as a body and mind practice and as an expression of new lifestyles; the Contact Improvisation basic training as an athletic technique and choreographic study (with reference to S. Paxton). The interdisciplinary perspective includes the sociology and anthropology of the body and physical activity, the philosophy of sport and the environmental sensitivity of contemporary public culture.